The Influence of Price, Product Quality, Brand Image towards Customers Buying Decision on Citra Pesona Shop - Winda Agusriana Sari; Yudi Prayoga; Rizki Syahputra (PT Mattawang Mediatama Solution, 2022)
This study aims to analyze the Influence of Price, Product Quality, and Brand Image Towards Buyer Decisions In Stores Image Charm and know the connection and contribution of every factor influencing purchase decisions on Shop Image Charm. The method in This research is quantitative. In this research, the population is customers of Shop Image Charm, with as many as 100 respondents. Method analysis data conducted is linear regression simple, and Test Hypothesis (Partial test, Simultaneous test, and Coefficient of Determination). The results of the t-test show that the independent variables Price and Product Quality affect the Purchase Decision partially (own) seen from the comparison score Sig which is smaller than 0.05 and score t-count bigger from t-table. In contrast, the Brand image variable has no partial effect (by itself). To the Purchase Decision at the Citra Pesona Store. Based on the test results Simultaneously, it is known that the value of Sig (0.000) is less than (0.05), and if the value of f count (41.899) is greater than the value of f table (2.70) then it can be seen that the Price, Product Quality, and Brand Image Together (simultaneously) have an effect positive and significant to Buying Decision on Image Shop Charm